اغتراب الذات وانبهارها بالآخر في الرواية السورية - يســير, خالــد عمر; الشـبلي, إبراهيم خليل (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يتناول البحث علاقة الذات بالآخر في الرواية السورية (2000-2010)عبر انبهارها به، ويقف على تحديد الأسباب التي أدّت إلى إحساس الذات بالاغتراب، ويظهر آليّات تعبير السرد الروائي عن أشكال الاغتراب الذي عانت منه الذات في ظل المواجهة الحضارية مع الآخر، والذي شكّل تحدِّيا كبيرا لها. This search handles the image of the "other" in the Syrian novel, and aims to show the relationship between the self and the "other" through the focusing on the self-alienation of the "other". Also, this search analyzes the reasons leading to that feeling of self-alienation, and shows the ways of expressing the different types of alienation in the novel's context that cause the suffering of the self in its civilized battle with the "other". This battle which forms a large challenge to it.